(untitled) (International Journal of Engineering and Computer Science, 2017)
Clothing is not only used to cover the body but is also a part and parcel of decoration as it includes painting, dyeing, printing and embroidery. Embroidery is one of the oldest forms of surface ornamentation of fabrics and garments. Embroidery is like ornamentation which gives elegance and grace to a piece of clothing. It is an art of beautiful drawing, harmonious color and elaborate needle skill. The embroideries in India are many and varied. The word ‘motif designing’ refers to the total composition of lines, forms, colours, shapes and textures in a decorative manner. Technological advancements have brought computer aided designing system in all the areas including textile and garment industry. Five motif designs suitable for clothes such as ’salwar’ , ’dupatta’, and skirt are developed in 2D and 3D software and by using C ++ programming. The integration of motif with clothes are presented by combining preferred motifs of different categories on the basis of visualization of designs suitable for cloth